Efficacy of using corticosteroids as adjunctive therapy in septic shock - Leite, Wellington Felipe; Medeiros Filho, Osman Batista de; Sousa, Milena Nunes Alves de (Brazilian Journal of Production Engineering, 2022)
Context: Septic shock is a state of acute circulatory failure combined with an infectious focus or with a predominance of an endotoxic component. Corticosteroid therapy has been used with the main focus on hypoperfusion. Corticosteroids are a class of drugs synthesized on the basis of endocrine steroid hormones, which are produced and secreted by the cortex of the adrenal glands. However, the efficacy and safety of corticosteroid therapy in septic shock remains uncertain, as there are both reports of clinical improvement and serious adverse effects, such as superinfection and metabolic and neuromuscular effects. Objective: Given the above, the present study aims to evaluate the effectiveness of adjuvant therapy with corticosteroids in patients with septic shock in order to look for scientific evidence showing benefits of this treatment, as well as to establish, if positive, the management of according to the evidence, of corticosteroids in this pathology. Method: It is characterized as an Integrative Review, in which the articles were selected on the Virtual Health Library platform, in which 460 articles were identified, but after applying the filters and selection criteria, 39 were selected among them. Results: The country that was the target of studies on such behavior was the United States. These studies were carried out more frequently in 2017, 2018 and 2019. After analyzing the data, it was suggested that this therapy was related to a faster reversal of shock and a reduction in the days of vasopressor use, in addition to decreasing the length of stay in the ICU. However, there are risks of adverse effects. Conclusion: Therefore, it was concluded that patients who are candidates for this treatment are those with greater severity and/or who do not respond primarily to resuscitation with fluids and vasoactive drugs. Furthermore, the use of these medications must be individualized, considering.